A Quantitative Approach to Data Collection and Analysis of ECHO Programs Focused on Cancer Care - Jennifer McBride; Patrick Edwards; Mindi Odom; Rich Killewald (Journal of Medical Education and Curricular Development)
Introduction The American Cancer Society (ACS) estimates over 2 million new cancer cases will be diagnosed in the United States in 2024. We utilize the Extension for Community Healthcare Outcomes (ECHO) Model ® developed by the University of New Mexico's ECHO Institute to address cancer-related knowledge gaps between healthcare professionals in underserved communities and specialists. By connecting healthcare professionals through a virtual telementoring community, ECHO programs are designed to increase local expertise and improve patient care. Methods This quantitative investigation evaluates the effectiveness of four ACS ECHO programs focused on cancer care across 2023 and 2024 by examining participants’ engagement, likelihood to use what was presented, as well as changes in knowledge and confidence. Results The ACS ECHO programs engaged 431 unique participants, averaging 108 participants per program. Of those participants, 59% were planning to use the information presented within a month. On average, participants’ knowledge and confidence had mean increases on a 5-point scale of +0.84 and +0.77, respectively, reflecting participants’ readiness and ability to apply what they learned into practice. Conclusion These findings can inform insights for promoting ECHO program sustainability and directions for future research, including integrating qualitative insights to deepen our contextual understanding of ACS ECHO program effectiveness. While previous evaluations of ECHO programs have solely relied on qualitative approaches, the quantitative methods used in this study can offer an objective approach to evaluating model implementation and program impact.